2015
DOI: 10.1164/rccm.201412-2233oc
|View full text |Cite
|
Sign up to set email alerts
|

FK506-Binding Protein 10, a Potential Novel Drug Target for Idiopathic Pulmonary Fibrosis

Abstract: Rationale: Increased abundance and stiffness of the extracellular matrix, in particular collagens, is a hallmark of idiopathic pulmonary fibrosis (IPF). FK506-binding protein 10 (FKBP10) is a collagen chaperone, mutations of which have been indicated in the reduction of extracellular matrix stiffness (e.g., in osteogenesis imperfecta).Objectives: To assess the expression and function of FKBP10 in IPF. Methods:We assessed FKBP10 expression in bleomycininduced lung fibrosis (using quantitative reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 46 publications
15
90
2
Order By: Relevance
“…We speculate that Fkbp10 silencing alters the quantity or crosslinking of the ECM and thereby alters mechanosensing. Consistent with our in vivo results, a prior in vitro study showed that inhibition of FKBP10 in primary human fibroblasts from pulmonary fibrosis patients attenuates expression of pro-fibrotic genes and decreases collagen secretion 36 . Thus, our findings expand the scope of Atp1a2 and Fkbp10 functions by demonstrating their novel roles in fibrogenesis in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…We speculate that Fkbp10 silencing alters the quantity or crosslinking of the ECM and thereby alters mechanosensing. Consistent with our in vivo results, a prior in vitro study showed that inhibition of FKBP10 in primary human fibroblasts from pulmonary fibrosis patients attenuates expression of pro-fibrotic genes and decreases collagen secretion 36 . Thus, our findings expand the scope of Atp1a2 and Fkbp10 functions by demonstrating their novel roles in fibrogenesis in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…A curated data analysis of these proteins showed upregulation of prominent pro-fibrotic markers such as COL1A2, COL3A1, COL5A1, FBN-C and many others ( Figure 2B). Consistent with other studies many TGFß1 regulated profibrotic markers such as THBS1 31 , THBS2 32 , VCAN and TNC 33 , FKBP10 34 were upregulated as well. Furthermore, significantly regulated proteins were subjected to pathway analysis using Cytoscape ( Supplementary Figure2B).…”
Section: Induction Of Pro-fibrotic Signalling Upon Tgfß1 Stimulation supporting
confidence: 91%
“…Immunoneutralization of IL-13 attenuated pulmonary fibrosis in bleomycin-induced pulmonary fibrosis (214) Moreover, pirfenidone decreased human lung fibroblast proliferation and differentiation into myofibroblasts by inhibiting TGF-β-induced phosphorylation of SMAD3 (221), while it has been shown ineffective in reducing collagen secretion in primary human lung fibroblasts in another study (222). Although, the initial report of the clinical trials was not concordant, CAPACITY-2, ASCEND, and a clinical trial performed in Japan demonstrated that pirfenidone slowed lung function decline and improved patient survival (223,224).…”
Section: Anti-il-13mentioning
confidence: 99%